JAG : The third season : Judge Advocate General - Elliott, David James, 1960-; Bell, Catherine, 1968-; Labyorteaux, Patrick, 1965-; Turner, Karri, 1966-; Jackson, John M.; CBS Studios Inc.; CBS Paramount Network Television (Firm); CBS DVD (Firm); Paramount Home Entertainment (Firm); LC Purchase Collection (Library of Congress) (Hollywood, Calif. : CBS DVD : Paramount Home Entertainment, 2007)
The men and women of the Navy's Judge Advocate General (JAG) Corps are back. In this season, Commander "Harm" Rabb and Major "Mac" MacKenzie both find romance but also suffer heartache. And while they might take on Cuban terrorists and Russian spies, they still manage to make it to the wedding between Bud and Harriet. 'JAG' digs deep to portray the human side of the military experience and show the bravery of those who give all for their country.
Disc 1: Ghost ship ; The court-martial of Sandra Gilbert ; The good of the service ; Blind side -- disc 2: King of the fleas ; Vanished ; Against all enemies ; Above and beyond -- disc 3: Impact ; People v. Rabb ; Defenseless ; Someone to watch over Annie -- disc 4: With intent to die ; Father's Day ; Yesterday's heroes ; Chains of command -- disc 5: The stalker ; Tiger, tiger ; Death watch ; Imposter -- disc 6: The return of Jimmy Blackhorse ; Clipped wings ; Wedding bell blues ; To Russia with love.
Originally broadcast on television during the 1997-1998 season.
Contains all 24 episodes from the third season.
David James Elliott, Catherine Bell, Patrick Labyorteaux, Karri Turner, John M. Jackson.
DVD; region 1; NTSC; full screen (1.33:1) presentation; Dolby Digital stereo., surround.
Closed-captioned.
Keywords: United States. -- Navy. -- Office of the Judge Advocate General -- Drama; Criminal investigation -- United States -- Drama; Legal television programs; Military television programs; Action and adventure television programs; Fiction television programs; Video recordings for the hearing impaired